Edukasi Modifikasi Perilaku Self Esteem Dalam Menurunkan Risiko Kesehatan Remaja Di SMAN 5 Kota Jambi Tahun 2025 - Veriza, Ervon; Abbasiah, Abbasiah; Upix, Desif; Ananda W, Shelly (Jurnal Salam Sehat Masyarakat (JSSM), 2025)
Adolescence is an important phase in the formation of identity, character, and life habits, so mental health, especially self-esteem, needs attention. In Indonesia, around 52% of adolescents have committed risky behaviors towards health, one of which is influenced by low self-esteem. This community service was carried out at SMAN 5 Jambi City to increase knowledge and positive behavior of adolescents related to the concept of self-esteem as a preventive effort against risky behavior. The method used is an interactive educational approach through group discussions, role plays, and simulations. The Wilcoxon test results showed a sig value of 0.000 (p<0.05), which means there is a significant difference in the level of knowledge before and after the intervention. Education is proven to be an effective health promotion strategy in shaping positive behaviors and increasing adolescent awareness. This program is recommended to be widely implemented in other schools in Jambi City to support the overall strengthening of adolescent self-esteem.